JOB CHARACTERISTICS AND LOCUS OF HOPE AMONG TEACHERS IN SELECTED PUBLIC SENIOR HIGH SCHOOLS IN CAGAYAN DE ORO CITY - Erlwinmer R. Mangmang, (Chelonian Research Foundation, 2024)
Abstract - The current study examines the gap of knowledge between Job Characteristics (Task Significance, Task Identity, Job Autonomy, Skill Variety, and Job Feedback) and Locus-of-Hope (internal, family, peer, and spiritual) among the 101 public senior high school teachers from Cagayan de Oro City. Public school teaching in the Philippines is one of the jobs being considered as very tasking, thus exploring this specific population character is fitting for the study. Person r product moment correlation was used to test the hypothesis of the present study. In relation to the hypothesis, Job Characteristics has no significant relationship towards Locus-of-Hope, however the External-peer locus had a weak relationship towards Job Characteristics. Furthermore, the results of the study showed that 51.43% had scores below 171 which suggest that they perceived their Job as not well-defined while the remaining 48.57% perceived their job to be well-defined. Results also suggest that the participants have scored highest in task significance which means that these participants see the sense of value of the job and lowest in job autonomy which means that the job restricts them to practice certain degree of freedom. In terms of the Locus-of-Hope, results showed that the respondents anchor more their hope in spirituality as it has the highest mean, and anchor less their hope to peer which has the lowest mean. The present study opened new sources of inquiry that can further explain the experience of public senior high school teachers not just in the concept of Job Characteristics and Locus-of- Hope but more so, on the relationship of these variables towards the different aspects of their experience.